Comparison of the concentration of trace metals (Ni, Zn, Co, Cu and Se), Fe, vitamins A, C and E, and lipid peroxidation in patients with prostate cancer - Ozmen, H; Erulas, FA; Karatas, F; Cukurovali, A; Yalcin, O (Walter de Gruyter Gmbh, 2006)
The anticarcinogenic and antioxidant properties of vitamins A, C, E and pro- or antioxidant properties of trace metals have recently attracted increased attention. We examined the levels of antioxidant vitamins ( A, C and E), selenium and malondialdehyde ( MDA), and trace metals ( Fe, Ni, Zn, Co and Cu) in patients with prostate cancer. In total, 41 subjects ( 21 controls and 20 prostate cancer patients) were included in the study. The levels of trace elements and Fe in whole blood were determined by atomic absorption spectrophotometry. Serum levels of Se were determined using a fluorimetric method, while a HPLC method was used for serum levels of vitamins and MDA. The levels of vitamins A and E were significantly lower and MDA levels were significantly higher ( p < 0.001) in patients with prostate cancer compared to controls. Serum vitamin C was significantly lower in patients with prostate cancer when compared to controls (p < 0.01). Moreover, Se and Zn levels were also significantly lower, and levels of Ni, Co, and Cu were higher (p < 0.001) in patients with prostate cancer than in controls. Fe levels were not significantly different in patients compared to controls (p < 0.05). Our findings, together with the results of previous animal studies, suggest that the administration of vitamins A, C, and E, and Se and Zn may be beneficial in the prevention and treatment of human prostate cancer.
Keywords: lipid peroxidation; prostate cancer; trace elements; vitamins